2019
DOI: 10.1073/pnas.1908052116
|View full text |Cite
|
Sign up to set email alerts
|

mRNA structure regulates protein expression through changes in functional half-life

Abstract: Messenger RNAs (mRNAs) encode information in both their primary sequence and their higher order structure. The independent contributions of factors like codon usage and secondary structure to regulating protein expression are difficult to establish as they are often highly correlated in endogenous sequences. Here, we used 2 approaches, global inclusion of modified nucleotides and rational sequence design of exogenously delivered constructs, to understand the role of mRNA secondary structure independent from co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
340
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(366 citation statements)
references
References 44 publications
26
340
0
Order By: Relevance
“…As more sources of structural data continue to be made available in higher quantity, resolution, and scope, the EternaBench and EternaFold frameworks will allow for the usage of these datasets in continually assessing and improving RNA structure prediction. An important use case for EternaFold will be computationally guided design of RNA medicines, including structured mRNAs 19 for viral pandemics like COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As more sources of structural data continue to be made available in higher quantity, resolution, and scope, the EternaBench and EternaFold frameworks will allow for the usage of these datasets in continually assessing and improving RNA structure prediction. An important use case for EternaFold will be computationally guided design of RNA medicines, including structured mRNAs 19 for viral pandemics like COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Cloud Labs (SHAPE-CE, SHAPE-MaP, DMS-MaP-seq vs. MAP-seq) and for distinct molecules, including viral genomes 21, 35-40 ribosomal RNAs40,41 , and mRNAs designed to improve protein expression19 (Table 2,…”
mentioning
confidence: 99%
“…Producing cell lines and clinical grade subunit protein typically takes more than 1 year, while manufacturing nucleic acid vaccines can be done in a matter of weeks 16,17 . In addition to advantages in manufacturing speed, mRNA vaccines are potently immunogenic and elicit both humoral and cellular immunity 1820 . Therefore, we evaluated mRNA formulated in lipid nanoparticles (mRNA/LNP) as a delivery vehicle for the MERS S-2P and found that transmembrane-anchored MERS S-2P mRNA elicited better neutralizing antibody responses than secreted MERS S-2P (Extended Data Fig.…”
Section: Figurementioning
confidence: 99%
“…mRNA levels don't always correspond to protein levels due to various factors, including post-transcriptional modification, mRNA stability, and regulation by miRNAs (Valencia-Sanchez et al, 2006;Nachtergaele and He, 2017;Nouaille et al, 2017;Mauger et al, 2019). Therefore, measuring protein levels during infection can provide a more direct functional relationship between the virus and the host (Koussounadis et al, 2015;Liu et al, 2016).…”
Section: Proteomics Studies In Hcmvmentioning
confidence: 99%